New chromatographic materials for the separation and concentration of uranium from environmental matrices - Horwitz, E.P.; Dietz, M.L.; Chiarizia, R.; Diamond, H. (Argonne National Laboratory, 1991)
Extraction chromatography, in which an inert support is impregnated with an extractant solution to form a chromatographic resin, combines the specificity of extraction with the ease of operation of an ion exchange column, thereby overcoming the principal drawbacks of the two methods when used alone. Previous work in this laboratory on the design of selective extractants for use in nuclear fuel reprocessing and in nuclear waste treatment has led to the development of several new phosphorus-based neutral organic extractants. In this report, we examine the use of two of these materials as stationary phases in extraction chromatography for the isolation of uranium from environmental samples. 2 refs., 2 figs., 1 tab.